Mucopolysaccharidosis type iv: report of 5 cases of morquio syndrome (2022)
Mucopolysaccharidosis type IV or Morquio Syndrome, is a lysosomal deposit disease, of autosomal recessive inheritance with a similar incidence in men and women. The clinical picture is of variable expressiveness, its phenotype is characterized by skeletal dysplasia that includes neck and short trunk, short stature, keel thorax, kyphosis, scoliosis, genus valgus, flat foot, coxa valga, gait disorders, instability of the cervical spine and wedge or ovoid vertebrae. The treatment is symptomatic, with enzyme replacement. We present a series of 5 cases, the product of 2 couples, with a confirmed diagnosis of Mucopolysaccharidosis type IV, and different clinical presentation.